Islamic Education Management Based on Local Wisdom and Global Competencies of Students - Hamdanah (Kartika: Jurnal Studi Keislaman, 2025)
This study explores how Islamic educational institutions in Indonesia integrate local wisdom (kearifan lokal) with global competencies to develop students who are both ethically grounded and globally competent. Using a qualitative research design, data were collected through semi-structured interviews, document analysis, and participant observation across three institutions representing traditional, modern, and hybrid models of Islamic education. The findings reveal that local wisdom shapes leadership, curriculum design, and pedagogical practices, fostering moral development, social responsibility, and cultural identity among students. Simultaneously, global competencies such as critical thinking, digital literacy, intercultural communication, leadership, and entrepreneurship are intentionally cultivated through innovative curricula and extracurricular programs. Effective integration is facilitated by participatory leadership, teacher professional development, and stakeholder engagement. The study highlights that balancing local wisdom with global competencies produces graduates who are ethically grounded, culturally aware, and capable of navigating global challenges. These findings provide insights for policymakers, educators, and institutional leaders seeking to achieve holistic, value-based education in the twenty-first century.